Β‐Thalassemia in childhood: Current state of health in a high‐income country. (6th January 2023) - Donze, Caroline; Benoit, Audrey; Thuret, Isabelle; Faust, Cindy; ,; Gauthier, Alexandra; Berbis, Julie; Badens, Catherine; Brousse, Valentine
Summary: β‐thalassemia is an haemoglobinopathy characterized by a defective synthesis of the β‐globin chain. To assess the current state of health of paediatric patients with β‐thalassemia, data from the French national registry regarding children born between 2005 and 2020 with β‐thalassemia intermedia (TI) or major (TM) were collected. A total of 237 patients (median age 7.1 years at last visit) were analysed, of whom 156 (65.8%) were born in France and 162 (68.4%) had a TM phenotype. The probability of survival for children with TM born in France was 98.3% at 15 years. Fifty‐four (22.8%) children received a haematopoietic stem cell transplant with a success rate of 88.8%. Hepatic and cardiac iron overload monitoring in non‐transplanted patients showed moderate overload in 15.7% (18/115) and 7.1% (7/99) of cases, respectively, while clinical complications were found in only 4 patients with TM (hepatic in 3 cases). At last visit, mean ferritinemia was 1293 ng/ml (±759). Overall, less than 10% of children underwent splenectomy. No significant impact of the disease on growth or academic achievement was observed. Deferasirox was the main first‐line chelator, prescribed in 78.2% of cases, with side effects reported in 11.7% of instances.